(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
This article explores the design and implementation of computer-based learning media workshops aimed at enhancing the competency of Arabic language teachers. It examines workshop curricula, pedagogical strategies, hands-on experiences, facilitation roles, and evaluation mechanisms. The study underscores the importance of cultural relevance and contextual appropriateness in workshop designs for educators in Islamic schools in Indonesia.The challenges faced during these workshops include practical barriers (limited device access), technological hindrances (varying proficiency levels), and pedagogical adjustments (resistance to change). Recognizing and addressing these challenges is crucial for refining future workshops and ensuring effective technology integration in language education.In conclusion, the transformative journey of improving Arabic language teachers’ competency through computer-based workshops faces diverse challenges, and understanding and addressing these obstacles are essential for successful technology-enhanced language education.